Use of the Trifunctional Cyclic Initiator, DEKTP, as the Radical Initiator in the Modification of Poly(propylene) in the Presence of Different Branching/Crosslinking Co‐Agents. Issue 1 (15th April 2013) - García, L.; Morales, G.; Avalos B, F.; Acuña, P.
Abstract: Homopolypropylene was modified in the molten state using a new cyclic multifunctional peroxide as the initiator, the Diethyl Ketone Triperoxide (DEKTP), in the presence of different branching/crosslinking co‐agents: Trimethylolpropane Triacrylate (TM), Trimethylolpropane Triacrylate Propoxylate (TMPP), Pentaerythritol Tetraacrylate (PETA) and N′N′‐1, 3‐Phenylene Dimaleimida (FDM). Experiments were carried out in an internal mixer at 180 °C, using two different concentrations of co‐agent/initiator; [0.250/0.025] and [0.50/0.05], molar rate = [co‐agent]/[initiator] constant equal to 10. The modified PP′s were evaluated by GPC, FTIR, DSC, WAXD, and MOP. Torque and MFI were also evaluated. The results showed the presence of branches in the backbone of PP when it was modified with TM and PETA.